1996
DOI: 10.1017/s0954579400007173
|View full text |Cite
|
Sign up to set email alerts
|

The connection of observed hostile family conflict to adolescents' developing autonomy and relatedness with parents

Abstract: This study examined the link between hostile conflict in families with adolescents and adolescents' efforts to establish autonomy and relatedness in interactions with parents in both normal and psychiatrically impaired groups. Longitudinal, observational data were obtained by coding family interaction tasks involving 53 adolescents and their two parents at age 14 and age 16 years. Measures were obtained for hostile adolescent-parent conflict, hostile marital conflict, and indices of adolescents' success or dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 32 publications
1
66
0
7
Order By: Relevance
“…In relation to mental health disorders expressed as externalising behaviours, it is suggested that insecure patterns of attachment may serve as predictors of anger and hostility towards one's parents, and thus decrease behavioural control, which is the main buffer of deviant behaviours among teenagers (Greenberg & Speltz, 1988;Patterson, DeBaryshe, & Ramsey, 1989). A relationship has been shown between attachment and behaviour disorders (Rosenstein & Horowitz, 1996) and deviant behaviours (Allen et al, 1996(Allen et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to mental health disorders expressed as externalising behaviours, it is suggested that insecure patterns of attachment may serve as predictors of anger and hostility towards one's parents, and thus decrease behavioural control, which is the main buffer of deviant behaviours among teenagers (Greenberg & Speltz, 1988;Patterson, DeBaryshe, & Ramsey, 1989). A relationship has been shown between attachment and behaviour disorders (Rosenstein & Horowitz, 1996) and deviant behaviours (Allen et al, 1996(Allen et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they may be differentially related to a number of different outcomes for teens, including functioning within their close relationships. Past research has suggested that autonomy inhibition is linked to a range of other components of the parent-adolescent relationship, such as less parent-teen involvement, poorer communication, less positive affective expression, and increased parent-adolescent conflict and hostility (Allen, Hauser, O'Connor, Bell, & Eickholt, 1996;Bulcroft, 1991;Collins, 1990;Smetana, 1995;Smetana & Berent, 1993). Although peer relationship outcomes have not been studied as extensively, similar patterns have been found: Autonomy promotion (on the part of either the parent or the adolescent) within the parent-adolescent relationship has been linked to increased interpersonal competence and more intimate friendships (Allen, Bell, & Boykin, 2000;Hall, 2002;McElhaney, 2000;McElhaney & Allen, 2001), whereas undermining of autonomy has been linked to decreased interpersonal competence, greater amounts of hostility in relationships with peers, and increasingly distant peer relationships (Allen et al, 2000;Allen & Hauser, 1993;Allen, Hauser, O'Connor, & Bell, 2002;McElhaney, 2000;Tencer, Meyer, & Hall, 2003).…”
mentioning
confidence: 99%
“…Les adolescents présentant le même niveau d'autonomie émotionnelle alors qu'ils se 77 sentent proches ou attachés à leurs parents possèdent une meilleure santé psychologique que leurs pairs (Allen, Hauser, O'Connor, Bell & Eickholt, 1996;Chen & Dornbusch, 1998;Fuhrman & Holmbeck, 1995;Lamborn & Steinberg, 1993;Ryan & Lynch, 1989).…”
Section: Relation Entre Comportements Interpersonnels Et Dépressionunclassified